Alpha thalassemia trait in a child with juvenile diabetes: a case report - Kunnummal, Manaal; Philip, Bincy; Cherian, Carol Sara (International Journal of Contemporary Pediatrics, 2025)
Alpha thalassemia trait (two missing α-globin genes) manifests as a microcytic anaemia that can be mistaken for iron-deficiency anaemia. A 12‑year‑old female child, who is a known case of type 1 diabetes mellitus presented with persistent microcytic hypochromic anaemia which failed to improve even after iron therapy. She was evaluated for her low haemoglobin values with the peripheral smear showing microcytic hypochromic anaemia which eventually was diagnosed as alpha thalassemia trait. This case reiterates the association between a metabolic disorder and a haemoglobinopathy, which is rarely reported in children.